ANALISIS MODEL PEMBELAJARAN COOPERATIVE LEARNING DALAM MENGEMBANGKAN KERJA SAMA SISWA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Najwa Aulia Kayen; Nadira Wati; Nike Alvionita; Nadia Aulia Rahma; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of cooperative learning in Social Studies (IPS) learning at the elementary school level, focusing on improving students’ learning activity and collaboration skills. The problem addressed in this research is the uneven participation of students in group discussions, where some students tend to be passive and less confident. This study aims to analyze the effectiveness of cooperative learning in enhancing student engagement and interaction during the learning process. The research employed a qualitative descriptive approach supported by simple quantitative data. Data were collected through interviews and observations involving teachers and fourth-grade students at SDN 01 Balai Batu Lima Kaum. The findings indicate that the implementation of cooperative learning has a positive impact on students’ learning activities, social interaction, and teamwork. The average level of student activeness reached 72.4%, categorized as good, with most students actively participating in discussions. However, several challenges were identified, including unequal participation among group members, limited self-confidence of some students, and difficulties in conducting individual assessment within group work. Overall, cooperative learning proves to be an effective strategy in creating an interactive and student-centered learning environment, although proper classroom management and evaluation strategies are required to optimize its implementation.